Effect of High-Risk Versus Low-Risk Pregnancy at the First Antenatal Care Visit On the Occurrence of Complication During Pregnancy and Labour Or Delivery in Kenya: A Double-Robust Estimation. - Kadengye, Damazo T.; Odero, Henry Owoko; Izudi, Jonathan (Kabale University, 2024)
Objectives We evaluated the causal effects of high-risk versus low-risk pregnancy at the first antenatal care (ANC) visit on the occurrence of complications during pregnancy and labour or delivery among women in Kenya. Methods We designed a quasi-experimental study using observational data from a large mobile health wallet programme, with the exposure as pregnancy risk at the first ANC visit, measured on a binary scale (low vs high). Complications during pregnancy and at labour or delivery were the study outcomes on a binary scale (yes vs no). The causal effects of the exposure were examined using a double-robust estimation, reported as an OR with a 95% CI. Results We studied 4419 women aged 10–49 years (mean, 25.6±6.27 years), with the majority aged 20–29 years (53.4%) and rural residents (87.4%). Of 3271 women with low-risk pregnancies at the first ANC visit, 833 (25.5%) had complications during pregnancy while 1074 (32.8%) had complications at labour/delivery. Conversely, of 1148 women with high-risk pregnancies at the first ANC visit, 343 (29.9%) had complications during pregnancy while 488 (42.5%) had complications at labour delivery. Multivariable adjusted analysis showed that women with high-risk pregnancy at the time of first ANC attendance had a higher occurrence of pregnancy during pregnancy (adjusted OR (aOR) 1.22, 95% CI 1.02 to 1.46) and labour or delivery (aOR 1.20, 95% CI 1.03 to 1.41). In the double-robust estimation, a high-risk pregnancy at first ANC visit increased the occurrence of complications during pregnancy (OR 1.23, 95% CI 1.04 to 1.46) and labour or delivery (OR 1.24, 95% CI 1.07 to 1.45). Conclusion Women with a high-risk pregnancy at the first ANC visit have an increased occurrence of complications during pregnancy and labour or delivery. These women should be identified early for close and appropriate obstetric and intrapartum monitoring and care to ensure maternal and neonatal survival.